The Impact of Anthropogenic Disturbance to the Canopy Microclimate of Tropical Forests in the Southern Western Ghats, India - Sagar, Rubin; Devy, M. Soubadra (Frontiers in Forests and Global Change, 2022)
Anthropogenic disturbances are a pressing driver of forest degradation, and are known to affect the microclimate within forests. Most organisms experience the microclimate and hence, associated changes may drive species communities in rainforests. However, such knowledge remains limited in the case of forest canopies, especially in South Asia. We aimed to identify differences in the temperature and light intensity, and beetles and vascular epiphytes in the canopy between old-growth and secondary forests. Using sensors, we recorded two key microclimatic variables, the air temperature and light intensity, in the crowns of 36 Cullenia exarillata A. Robyns trees. We sampled beetles (morphospecies) and vascular epiphytes (genera) in the crowns. We provide evidence that canopies of secondary forest stands (intensively logged 60 years ago) (1) continue to show higher canopy air temperatures and light intensity, and (2) have higher beetle abundance (individuals), richness (morphospecies) and diversity but lower vascular epiphyte abundance (individuals), richness (genera) and diversity as compared to primary forest stands. We also show that the beetle communities differ (with greater beta diversity in the primary forest), but the vascular epiphyte communities were similar between the two forest types. We hope that this information begins to bridge the gap in understanding the role of microclimate in driving species communities and the ecology of human-modified forests.